Effect of gender and training years on the upper extremity dynamic balance function in adolescent swimmers - Lu, Z.-A.; Lv, Z.-F.; Yang, Q.-H.; Du, S.-H.; Wang, Y.-C.; Zhang, Y.-H. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Upper extremity dynamic balance is the ability of the upper extremities to sustain stability during exercise. Abnormal upper extremity dynamic balance increases the risk of sport injury in swimmers. However, research on the influencing factors of upper extremity dynamic balance function is limited. This study aims to investigate the factors affecting upper extremity dynamic balance function in adolescent swimmers.